2018
DOI: 10.18280/ijht.360137
|View full text |Cite
|
Sign up to set email alerts
|

Research on thermal performance of external thermal insulation composite concrete wall block

Abstract: For the defects of temperature control performance and thermal property of existing concrete building walls, a new composite concrete wall block is proposed, and the thermal property of the block is calculated and analyzed. The transverse hole of designed H-shaped concrete block can be embedded with thermal insulation materials, and the vertical ribs are added to the traditional brick wall, which effectively increases the stability and thermal performance of the wall. The selected PCM concrete has better funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
1
0
1
Order By: Relevance
“…A esse respeito, Zhang et al (2018) propuseram dois modelos de bloco utilizando concreto PCM: um deles em forma de H e o outro com aparência quadrada. O concreto PCM apresentou uma melhor regulação de temperatura, o que contribuiu para o isolamento térmico e a parede em H demonstrou melhor desempenho em relação ao outro modelo, podendo comportar outros materiais isolantes térmicos.…”
Section: Desempenho Térmico Do Concretounclassified
“…A esse respeito, Zhang et al (2018) propuseram dois modelos de bloco utilizando concreto PCM: um deles em forma de H e o outro com aparência quadrada. O concreto PCM apresentou uma melhor regulação de temperatura, o que contribuiu para o isolamento térmico e a parede em H demonstrou melhor desempenho em relação ao outro modelo, podendo comportar outros materiais isolantes térmicos.…”
Section: Desempenho Térmico Do Concretounclassified
“…For intermittently heated spaces and for no heating conditions, the better position of insulation material for energy consumption reduction and indoor thermal comfort is on the interior wall surface [11]. It has been widely demonstrated that plant and regulation system retrofitting interventions are preferable because they are effective and with much lower overall costs than any intervention on the building envelope, especially if the building belongs to historical heritage [11][12]. Other studies show that the use of PMV as a parameter for the control strategy of a plant system leads to a considerable energy saving in comparison with the use of a fixed set-point range of indoor air temperature [13].…”
Section: Introductionmentioning
confidence: 99%